(untitled) (Revista Internacional de Formação de Professores, 2020)
This paper presents reflection on bridges and gaps in the relationship between teacher training processes and the development of the primary education curriculum in Angola. From a dialectical-reflexive and critical perspective, we discuss the need for teacher training that can be combined with the educational context of contemporary. Thus, this study questioned the problematic and complex relationship between the curricular design of teacher education and the development of the primary education curriculum in Angola, which require a perspective of globalization and contextualization of training, using new technologies, able to guarantee the educational quality in Angola